Modeling residential indoor concentrations of PM2.5, NO2, NOx, and secondhand smoke in the Subpopulations and Intermediate Outcome Measures in COPD (SPIROMICS) Air study. (28th December 2020) - Zusman, Marina; Gassett, Amanda J.; Kirwa, Kipruto; Barr, R. Graham; Cooper, Christopher B.; Han, MeiLan K.; Kanner, Richard E.; Koehler, Kirsten; Ortega, Victor E.; Paine 3rd, Robert; Paulin, Laura; Pirozzi, Cheryl; et al.
Abstract: Increased outdoor concentrations of fine particulate matter (PM2.5 ) and oxides of nitrogen (NO2, NOx ) are associated with respiratory and cardiovascular morbidity in adults and children. However, people spend most of their time indoors and this is particularly true for individuals with chronic obstructive pulmonary disease (COPD). Both outdoor and indoor air pollution may accelerate lung function loss in individuals with COPD, but it is not feasible to measure indoor pollutant concentrations in all participants in large cohort studies. We aimed to understand indoor exposures in a cohort of adults (SPIROMICS Air, the SubPopulations and Intermediate Outcome Measures in COPD Study of Air pollution). We developed models for the entire cohort based on monitoring in a subset of homes, to predict mean 2‐week–measured concentrations of PM2.5, NO2, NOx, and nicotine, using home and behavioral questionnaire responses available in the full cohort. Models incorporating socioeconomic, meteorological, behavioral, and residential information together explained about 60% of the variation in indoor concentration of each pollutant. Cross‐validated R 2 for best indoor prediction models ranged from 0.43 (NOx ) to 0.51 (NO2 ). Models based on questionnaire responses and estimated outdoor concentrations successfully explained most variation in indoor PM2.5, NO2, NOx, and nicotine concentrations.